The Transportation Agency's Strategy in Managing Parking Lots on Jalan K.H. Fakhruddin, Samarinda City - Faradilla Ramadhany; Muhammad Arif Nurrahman (Universitas Negeri Gorontalo, 2025)
This study aims to formulate alternative strategies to improve the effectiveness of parking management by the Transportation Agency on K.H. Fakhruddin Street in Samarinda City. The main problem is the suboptimal management of parking, which is characterized by rampant illegal parking, weak supervision, and low public awareness of parking regulations. This study uses a mixed methods approach with a concurrent embedded model, where qualitative data is the main focus, while quantitative data is used as supporting evidence. Qualitative data was obtained through observation, interviews, and documentation, while quantitative data was collected simply through scores on the IFAS and EFAS tables to reinforce the strategic position. Both types of data were analyzed simultaneously to obtain a more comprehensive understanding. SWOT analysis was used to identify internal and external factors that influence parking management. The results of the study show that the strategic position is in Quadrant I (aggressive strategy), so it is necessary to maximize strengths and opportunities. Recommended alternative strategies include the implementation of technology-based surveillance such as CCTV, the formation of a community-based surveillance team, the addition of parking spaces through cooperation, and the relocation of parking to Taman Bebaya with ongoing socialization